Analysis of the degradation of highefficiency encapsulated PM6:Y7based Photovoltaic Cells - Królak, Patrycja (2023)
In this work, we report a degradation study of high-efficiency conventional polymer solar cells (PSCs). The high performance of the PM6:Y7-based device is achieved with a power conversion efficiency (PCE) of up to 15.64% in the first measurement. The article describes the results of the measurements and analysis of the degradation process. The electrical parameters during the degradation process were extracted from the current density – voltage characteristics curves (J–V) under light and dark conditions. Were observed the specific parameters of the selected cells: open-circuit voltage (VOC), short circuit current density (JSC), fill factor (FF), PCE, series (RS), and shunt (RSH) resistance values The PCE of the device decreased down to 64% of the initial PCE after 1056 h.